Penerapan Kewajiban Notaris dalam Memberikan Pelayanan Hukum bagi Pihak Kurang Mampu - Sectiona, Wiky; Hafidh, Muhammad (Universitas Muhammadiyah Ponorogo, 2025)
In Indonesia, the Notary profession is a legal entity that has the authority to provide legal services according to the law. This authority is stated in Law of the Republic of Indonesia No. 2 of 2014 and No. 30 of 2004. However, notaries are not only responsible for providing legal services to the rich but also to the poor, in accordance with the principle of social justice. This study aims to analyze the application of notary law in providing legal services to the poor and to identify the challenges faced by notaries in their work. The research method used is Normative Jurisprudence or library legal research method, namely reviewing laws and regulations related to notary obligations, such as the Notary Law (UUJN), the Regulation of the Minister of Law and Human Rights, as well as the notary code of ethics and relevant case studies regarding notary obligations to provide legal services. The data obtained will be analyzed using a descriptive-qualitative method, namely by describing, interpreting and concluding the results of the study based on the data collected. The results show that although the obligation of notaries to provide legal services for the underprivileged has been regulated by law, its implementation still faces various obstacles. Strengthening of regulations, incentive systems, and better supervision are needed so that these services can truly be enjoyed by the people in need.